Smart Label with Color Indicator Made of Purple Sweet Potato (Ipomoea Batatas L.) on The Bottle Packaging of Pasteurized Milk - Andrew Setiawan Rusdianto; Desita Wirda Ramadhan (Food, Agriculture and Natural Resources - NETWORKS, 2021)
Smart label has made it possible to monitor and communicate information about the quality of packaged foods. Smart label is immobilized with natural dyes that are sensitive to changes in pH, namely anthocyanins. The product used in this research is pasteurized milk. The pH quality of milk will affect the storage temperature. The purpose of this study was to develop a prototype smart label of purple sweet potato’s anthocyanin extract and to determine the feasibility of a smart label on the packaging as an indicator of milk freshness. Purple sweet potato extract was obtained by the maceration method using 96% ethanol and aquadest, which was acidified with acetic acid. The anthocyanin extract had a pH value of 5.60 ± 0.015 and an anthocyanin value of 70,163 ± 0.889 mg/100 g. The smart label shows milk freshness indicated by the changes in color. While a purple color indicates fresh milk, a faded purple color indicates that the milk is fairly fresh, and a reddish-purple smart label indicates the milk is not fresh. At room temperature storage, stale milk at 12 hours has a pH value of 5.84 ± 0.022 and a total microbe of 5.81 log10 or 6.5 x 105. In cold storage, stale milk on day 6 has a pH value of 5.92 ± 0.017 and a total microbe of 6.08 log10 or 1.2 x 106. The results of the feasibility of smart labels on pH stability indicate color changes in both acidic and alkaline conditions, but more stability is evident in acidic conditions.